Kajian Efektivitas Implementasi Program Demonstration Farm di Kecamatan Blanakan Kabupaten Subang - Sofyan Rahman; Aida Vitayala S Hubeis; Wini Trilaksani (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
In recent years, shrimp farming have experienced a variety of problems, both technical and non-technical, causing the shrimp farm do not work properly (idle). In 2012 the Ministry of Maritime Affairs and fisheries formulate revitalization program which focused on the rehabilitation ponds channel through Demonstration Farm (Demfarm) program. The purpose of this study is to analyze the effectiveness of the implementation of the Demfarm program in the Blanakan District in Subang regency. The data has been analyze using qualitative analysis, quantitative analysis, SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats), and AHP (Analytical Hierarchy Process). The result of the study shows that Demfarm implementation in Blanakan District, Subang Regency is quite effective. Blanakan District in Subang Regency is an ideal area for shrimp farm, the application of Demfarm technology can improve the productivity of farms  from 0-17  up to 7-75 tons / ha, the programs also help to establish the partnership system between farmers and the private sector. Shrimp farms have 0.148 IFE and 0.495 EFE, another most important thing for shrimp farming development in the Blanakan District is technology have 0.341. Shrimp farming worth to be developed, the value of Benefit Cost Ratio (B/C ratio) > 1, the Net Present Value (NPV) generated > 0 Break Event Point (BEP) the lowest production 7000 kg and the highest production is 7.500 kg, for BEP the lowest price is Rp60 000 and the highest price is Rp70.000